The Periodontal Pathogen Fusobacterium nucleatum Exacerbates Alzheimer’s Pathogenesis via Specific Pathways - Wu, Hongle; Qiu, Wei; Zhu, Xiaofang; Li, Xiangfen; Xie, Zhongcong; Carreras, Isabel; Dedeoglu, Alpaslan; Van Dyke, Thomas; Han, Yiping W.; Karimbux, Nadeem; Tu, Qisheng; Cheng, Lei; et al. (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is the most common form of dementia in older adults and has a devastating impact on the patient’s quality of life, which creates a significant socio-economic burden for the affected individuals and their families. In recent years, studies have identified a relationship between periodontitis and AD. Periodontitis is an infectious/inflammatory disease that destroys the supporting periodontal structure leading to tooth loss. Dysbiosis of the oral microbiome plays a significant role in the onset and development of periodontitis exhibiting a shift to overgrowth of pathobionts in the normal microflora with increasing local inflammation. Fusobacterium nucleatum is a common pathogen that significantly overgrows in periodontitis and has also been linked to various systemic diseases. Earlier studies have reported that antibodies to F. nucleatum can be detected in the serum of patients with AD or cognitive impairment, but a causal relationship and a plausible mechanism linking the two diseases have not been identified. In this study, we conducted both in vivo and in vitro experiments and found that F. nucleatum activates microglial cells causing morphological changes, accelerated proliferation and enhanced expression of TNF-α and IL-1β. In our in vivo experiments, we found that F. nucleatum-induced periodontitis resulted in the exacerbation of Alzheimer’s symptoms in 5XFAD mice including increased cognitive impairment, beta-amyloid accumulation and Tau protein phosphorylation in the mouse cerebrum. This study may suggest a possible link between a periodontal pathogen and AD and F. nucleatum could be a risk factor in the pathogenesis of AD. We are currently further identifying the pathways through which F. nucleatum modulates molecular elements in enhancing AD symptoms and signs.